(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
Background: The healthcare system in Iraq has been significantly affected by the events of the last few decades. The effects of various wars, internal conflicts, international sanctions, and political instability had also devastated the nation and its healthcare system. Materials and Methods: This is a cross-sectional study done at 23 randomly chosen (multistage random sampling) health centers in Babylon Province. Data were gathered during the period beginning from the third of January 2021 until the first of March 2021. Results: This study demonstrates that 87.0% of health centers had no medical staff trained in nutrition programs according to standards. While 95.7% of HCs had health staff trained in nutrition programs according to the same standards. As for the evaluation of nutrition services provider’s performance, the study showed that most health centers had moderate scores for most indicators. Conclusion: The current study showed that nutrition services were moderate in the health centers, despite the availability of supplements, guidelines and registers in most health centers.